Triple Helix Partnership Model Between Universities, Industry, and Government for Implementing an Outcome-Based Curriculum in the Era of Disruption at PTSP UNY: An Internal University Review - Ravena Rusma Ardita; Sutarto; Basanta Prasad Adhikari (Universitas Negeri Yogyakarta, 2025)
Background: This study aims to describe: (1) the ideal triple helix model (THM) partnership for implementing an outcome-based curriculum (OBC) in the era of disruption from the university's perspective; (2) the level of THM implementation according to the university's perspective; (3) the THM ecosystem implemented by the university; (4) the level of university role implementation within the THM framework. Method: This study employed both quantitative and qualitative descriptive research methods. Data collection techniques included a survey and a focus group discussion (FGD). The research subjects consisted of four active lecturers from PTSP FT UNY who provided survey responses, and seven PTSP lecturers participated in the FGD. Quantitative data were analyzed using descriptive statistical techniques, while qualitative data were examined through an interactive analytical model. Results: (1) The balanced triple helix Model (BTM) was identified as the ideal framework for implementing OBC, rated highly suitable with a score of 3.50, as it ensures a balanced role among all parties. (2) The THM implementation was mostly realized (score 2.80), involving industry, professional associations, and certification bodies. (3) The THM ecosystem was mostly established (score 2.84), with additional support from unlimited research and partnership funding. (4) The university’s role within THM was fully realized (score 3.02) through seminars, soft skill training, and certification programs. Conclusion: Based on the research findings, BTM is the ideal model for implementing OBC in the era of disruption. Furthermore, the implementation of the triple helix partnership model, ecosystem, and university roles is largely accomplished.